Integrative Negotiation Strategy to Fulfill Consumer Rights at PT. Ebad Alrahman Tourism Juanda Sidoarjo - Setiawan, Nadya Safirasari; Hakim, Ahmad Khairul (Munazzama: Journal of Islamic Management and Pilgrimage, 2022)
This research aims as a means of information related to integrative negotiation strategies in the fulfillment of consumer rights during the cancellation of hajj departures in two thousand and twenty-one years. Researchers use this type of qualitative research. In the process of qualitative data collection, researchers use phenomenological methods and inductive data analysis. Researchers used four research sources, namely: customer service, hajj handling, hajj administration, and hajj sales marketting. The results proved that integrative negotiation strategies have a significant influence on the fulfillment of consumer rights at the time of cancellation of hajj departures in two thousand and twenty-one years. Pilgrims can find a resolution to the conflict with PT. Ebad Alrahman Wisata Juanda Sidoarjo through three concepts of integrative negotiation strategies. Two negotiators take three approaches to integrative negotiation strategies: steps, methods, and success factors. The account sheet is the result of an integrative agreement between hajj pilgrims and PT. Ebad Alrahman Wisata Juanda Sidoarjo. PT. Ebad Alrahman Wisata Juanda Sidoarjo emphasized communication as a success factor in integrative negotiation strategies. PT. Ebad Alrahman Wisata Juanda Sidoarjo uses four online digital applications, such as: whatsapp, instagram, facebook, and the official website of www.ebadwisata.com.